Positive electrode material, preparation method thereof and lithium ion battery

By using a cladding layer containing lithium cobalt oxide on the high-nickel nickel-cobalt aluminum-based ternary cathode material, combined with a specific proportion of Co and Al elements, the problem of insufficient material stability and lithium ion deintercalation performance is solved, and efficient lithium ion battery performance and safety improvement is achieved.

CN119890276AInactive Publication Date: 2025-04-25JIANGSU TENPOWER LITHIUM
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510361863.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-26
Publication Date
2025-04-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

High-nickel nickel-cobalt-aluminum-based ternary cathode materials have shortcomings in terms of stability and lithium ion deintercalation performance, and conventional metal oxide coating may lead to lithium ion deintercalation hindering and ohmic heat accumulation, reducing safety performance.

Method used

A cladding layer containing lithium cobalt oxide is used, and the LiCoO2 content in lithium cobalt oxide is greater than 75 wt.% and combined with a specific content of Co elements and X elements (mainly Al elements), the mass ratio of Co elements and X elements in the cladding layer is between 25% and 50%. Through the optimization of sintering temperature and time, a stable cladding layer is formed.

Benefits of technology

It improves the stability of the cathode material and lithium ion deintercalation performance, reduces ohmic heat accumulation and safety risks, achieves a high capacity retention rate and prolongs battery cycle life, while avoiding the risk of premature battery failure and explosion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119890276A_ABST
    Figure CN119890276A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of batteries, and relates to a positive electrode material, a preparation method thereof and a lithium ion battery. The positive electrode material comprises a positive electrode inner core and a coating layer coating the surface of the positive electrode inner core, the chemical composition of the positive electrode inner core is Li [alpha] Ni [x] Co [y] Al [z] A [m] O [2], the coating layer contains an element Co and an element X, and the mass ratio of the element X in the coating layer to the element Co in the coating layer is 25%-50%; x is a metal element different from Co, and 50 wt.% or more of X is an Al element; the coating layer comprises a lithium cobalt oxide, and the lithium cobalt oxide comprises LiCoO2 with the content of more than 75 wt.%; and the content of the Co element in the coating layer is 4,000 ppm to 8,000 ppm. According to the invention, while the crystal structure is stabilized, the transmission of lithium ions is facilitated, the ohmic heat accumulation is reduced, the gas production is reduced, and the safety performance of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of batteries and relates to a positive electrode material and a preparation method thereof and a lithium ion battery. Background Art

[0002] As batteries are used more and more widely in life and production, people have put forward higher and higher requirements for battery performance, such as high capacity density, long cycle life and good safety. Compared with lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide, etc., ternary cathode materials have the advantages of high energy density and good rate performance, and have attracted the attention of many researchers. Among them, high-nickel nickel-cobalt-aluminum-based ternary cathode materials have higher energy density, but at the same time, they also show problems such as reduced stability.

[0003] In the prior art, the stability of high-nickel nickel-cobalt-aluminum-based ternary positive electrode materials is generally improved by coating. However, conventional metal oxide (such as Al2O3, ZrO2) coating may hinder the deintercalation of lithium ions. Moreover, the interface problems of the coating may cause the accumulation of ohmic heat and reduce safety performance.

[0004] Therefore, providing a modified material for high-nickel nickel-cobalt-aluminum-based ternary positive electrode materials, while retaining their intrinsic advantages, improving their stability and ensuring good lithium ion insertion and extraction performance and safety, is a technical problem that needs to be solved urgently. Summary of the invention

[0005] In view of the above technical problems existing in the prior art, the object of the present invention is to provide a positive electrode material and a preparation method thereof and a lithium ion battery.

[0006] To achieve the above object, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a positive electrode material, the positive electrode material comprising a positive electrode core and a coating layer coated on the surface of the positive electrode core, the chemical composition of the positive electrode core is Li α Ni x Co y Al z A m O2, 1≤α≤1.05, 0.80≤x≤0.95, 0.04≤y≤0.15, 0.005≤z≤0.06, 0≤m≤0.02, x+y+z+m=1, wherein A includes one or more of Zr, Mg, Sr, Y, La, Nb, Ba and Ti.

[0008] The coating layer contains Co element and X element, and the mass ratio of X element in the coating layer to Co element in the coating layer is 25% - 50%; X is a metal element different from Co, and more than 50wt.% of X is Al element.

[0009] The coating layer includes lithium cobalt oxide, and the lithium cobalt oxide includes LiCoO2 with a content greater than 75wt.%.

[0010] Based on the total mass of the positive electrode core, the content of Co element in the coating layer is 4000ppm - 8000ppm.

[0011] Preferably, X is 100% Al element. Therefore, the coating layer contains Co element and Al element, and the mass ratio of Al element in the coating layer to Co element in the coating layer is 25% - 50%.

[0012] Preferably, the total mass ratio of Co element and X element in the coating layer to the total mass of metal elements in the coating layer is more than 90%, and more preferably 95%. In the present invention, if other metals and other trace metal doping are not considered, Co element and X element in the coating layer of the present invention can account for nearly 100% of the total metal elements in the coating layer.

[0013] Preferably, when X is selected as 100% Al element, the total mass ratio of Co element and Al element in the coating layer to the total mass of metal elements in the coating layer is more than 90%, and more preferably 95%. In the present invention, if other metals and other trace metal doping are not considered, Co element and Al element in the coating layer of the present invention can account for nearly 100% of the total metal elements in the coating layer.

[0014] The following are the preferred technical solutions of the present invention, but do not limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved.

[0015] Preferably, the lithium cobalt oxide includes LiCoO2 and Li x Co 1-x O, 0 < x < 1, and the content of LiCoO2 is greater than 76wt.% and less than 100wt.%, or the lithium cobalt oxide is 100wt.% LiCoO2.

[0016] Preferably, the mass ratio of X element in the coating layer to Co element in the coating layer is 25% - 45%.

[0017] Preferably, X also includes other coating elements, and the other coating elements are one or more of W, Ti, and Ce.

[0018] In a second aspect, the present invention provides a method for preparing the positive electrode material as described in the first aspect, the preparation method comprising the following steps:

[0019] The positive electrode core and the coating source are mixed and then sintered, and the sintering temperature is greater than 500° C. and less than or equal to 800° C. to obtain the positive electrode material.

[0020] The coating source includes a cobalt source and an X source, the X source includes an aluminum source, and more than 50 wt.% of X is Al element.

[0021] Preferably, the cobalt source includes at least one of cobalt oxide, cobalt hydroxide and cobalt oxyhydroxide.

[0022] Preferably, the aluminum source includes at least one of aluminum oxide, aluminum hydroxide and aluminum oxyhydroxide.

[0023] Preferably, the X source further includes other coating sources, and the elements in the other coating sources are at least one of W, Ti and Ce.

[0024] Preferably, the other coating source is at least one of nitrate, chloride, hydroxide or oxide.

[0025] Preferably, the sintering is performed in an oxygen-containing atmosphere.

[0026] Preferably, the sintering time is 6h~24h.

[0027] Preferably, after the sintering is completed, the temperature is lowered at a cooling rate of 0.01° C. / min to 3° C. / min.

[0028] Preferably, the method for preparing the positive electrode core comprises the following steps:

[0029] The nickel-cobalt hydroxide, the doping source and the lithium source are mixed and sintered to obtain the positive electrode core.

[0030] The doping elements in the doping source include Al and A, wherein A includes one or more of Zr, Mg, Sr, Y, La, Nb, Ba and Ti.

[0031] Preferably, during the preparation of the positive electrode core, the molar ratio of each element satisfies Li / (Ni+Co+Al+A) of 1 to 1.05.

[0032] Preferably, during the preparation of the positive electrode core, the sintering temperature is 400°C to 1000°C.

[0033] Preferably, during the preparation of the positive electrode core, the sintering time is 6 h to 20 h.

[0034] In a third aspect, the present invention provides a lithium-ion battery, comprising a positive electrode, a negative electrode and a separator, wherein the positive electrode comprises the positive electrode material described in the first aspect.

[0035] Compared with the prior art, the present invention has the following beneficial effects:

[0036] The positive electrode material of the present invention uses a high-nickel type nickel-cobalt-aluminum-based ternary positive electrode material as the core, which has good rate performance under high voltage, and further introduces lithium cobalt oxide into the coating layer. Since the lithium cobalt oxide has a content of more than 75wt.% of LiCoO2, its layered structure is conducive to lithium ion deintercalation, good kinetic performance, interface impedance is basically consistent with the bulk phase, and ohmic heat accumulation is small; at the same time, considering that the interface has the properties of LiCoO2, it is easy to collapse the structure and electrolyte side reactions under high voltage conditions. To address this problem, the present invention can stabilize the crystal structure and not deteriorate ohmic heat by matching a specific content of Co element and controlling the mass ratio of X element to Co element. The battery assembled with the positive electrode material of the present invention has a high capacity retention rate on the one hand, which is above 84%; on the other hand, the appropriate CID opening time can be controlled between 750s and 820s, which not only avoids premature failure of the battery, but also avoids the risk of battery explosion. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 This is a scanning electron microscope image of the positive electrode material with a coating layer provided in Example 1. DETAILED DESCRIPTION

[0038] The technical solution of the present invention is further described below with reference to the accompanying drawings and through specific implementation methods.

[0039] The specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0040] In a cylindrical lithium-ion battery, a winding core is formed by stacking a positive electrode sheet, a separator, a negative electrode sheet, and a separator in this order and winding them up, and is housed in a battery case in a state of being impregnated with an electrolyte.

[0041] In one embodiment, a positive electrode active material layer is coated on both sides of a positive electrode foil to form a positive electrode sheet. The positive electrode foil may be a metal foil made of aluminum or an aluminum alloy.

[0042] In one embodiment, negative electrode active material layers are coated on both sides of the negative electrode foil to form a negative electrode sheet. The material of the negative electrode foil may be a metal foil made of copper or a copper alloy.

[0043] In one embodiment, the separator may be any separator known in the prior art of lithium-ion batteries.

[0044] In one embodiment, the negative electrode material may be a carbon material, such as a graphite material, wherein the graphite material may be artificial graphite and / or natural graphite, preferably a graphite composite negative electrode material doped with a certain amount of silicon oxygen or silicon carbon.

[0045] In one embodiment, the separator can be a PE film, a PP film or a composite film, wherein the composite film includes at least two of the PP film, the PE film and the PP film. Of course, in one embodiment, the separator can also be a ceramic-coated porous film.

[0046] In one embodiment, the electrolyte solution includes a solvent and an electrolyte salt.

[0047] In one embodiment, the solvent comprises any one or more of non-aqueous solvents such as organic solvents. The electrolyte of the non-aqueous solvent is a so-called non-aqueous electrolyte, and the non-aqueous solvent may be, for example, cyclic carbonate, chain carbonate, lactone, chain carboxylate, nitrile, etc. In addition, the electrolyte may further comprise any one or more of other materials such as additives.

[0048] In one embodiment, the electrolyte salt may include any one or more of a lithium salt or the like. In addition, the electrolyte salt may also include a salt other than a lithium salt. The salt other than a lithium salt may be a light metal salt other than lithium, for example.

[0049] In one embodiment, the battery shell is a metal shell, which may be a steel shell or an aluminum shell, and is more preferably a steel shell.

[0050] In the present invention, the size of the cylindrical battery can be 18650, 21700 and other models.

[0051] Preferably, the following test of the present invention is performed on a 18650 cylindrical battery cell.

[0052] In one embodiment of the present invention, a positive electrode material is provided, the positive electrode material comprising a positive electrode core and a coating layer coated on the surface of the positive electrode core, the chemical composition of the positive electrode core is Li α Ni x Co y Al z A m O2, 1≤α≤1.05, 0.80≤x≤0.95, 0.04≤y≤0.15, 0.005≤z≤0.06, 0≤m≤0.02, x+y+z+m=1, wherein A includes one or more of Zr, Mg, Sr, Y, La, Nb, Ba and Ti;

[0053] The coating layer contains Co and X elements, the mass proportion of the X element in the coating layer relative to the Co element in the coating layer is 25% to 50%; X is a metal element different from Co, and more than 50wt.% of X is Al element;

[0054] The coating layer includes lithium cobalt oxide, and the lithium cobalt oxide includes LiCoO2 with a content greater than 75wt.%;

[0055] Based on the total mass of the positive electrode core, the content of the Co element in the coating layer is 4000ppm~8000ppm.

[0056] In one embodiment of the present invention, 1≤α≤1.05, for example, 1, 1.01, 1.02, 1.03, 1.04 or 1.05; 0.80≤x≤0.95, for example, 0.80, 0.82, 0.83, 0.85, 0.88, 0.89, 0.90, 0.92, 0.93, 0.94 or 0.95; 0.04≤y≤0.15, for example, 0.04, 0.06, 0.07, 0.18, 0.20, 0.21, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29, 0.30, 0.31, 0.32, 0.33, 0.34, 0.35, 0.36, 0.37, 0.38, 0.39, 0.40, 0.41, 0.42, 0.43, 0.44, 0.45, 0.46, 0.47, 0.48, 0.49, 0.50, 0.51, 0.52, 0.08, 0.10, 0.12, 0.13, 0.14 or 0.15, etc.; 0.005≤z≤0.06, for example, it can be 0.01, 0.02, 0.03, 0.04, 0.05 or 0.06, etc.; 0≤m≤0.02, for example, it can be 0, 0.001, 0.003, 0.005, 0.007, 0.008, 0.01, 0.012, 0.015, 0.017 or 0.02, etc. Wherein, when m is 0, it means that the chemical composition does not contain element A.

[0057] In one embodiment of the present invention, the mass proportion of the X element in the coating layer relative to the Co element is 25% to 50%, for example, it can be 25%, 27%, 28%, 30%, 32%, 34%, 36%, 38%, 40%, 42%, 43%, 45%, 47%, 48% or 50%.

[0058] In one embodiment of the present invention, the content of Co element in the coating layer is 4000ppm~8000ppm, for example, it can be 4000ppm, 4250ppm, 4500ppm, 4700ppm, 5000ppm, 5200ppm, 5400ppm, 5600ppm, 5800ppm, 6000ppm, 6250ppm, 6500ppm, 6800ppm, 7000ppm, 7250ppm, 7500ppm, 7700ppm, 7800ppm or 8000ppm.

[0059] The cathode material of one embodiment of the present invention uses a high-nickel nickel-cobalt-aluminum-based ternary cathode material as the core, which has good rate performance at high voltages. Further, lithium cobalt oxide is introduced into the coating layer. Since the lithium cobalt oxide contains more than 75 wt.% of LiCoO2, its layered structure is conducive to the insertion and extraction of lithium ions, with good kinetic performance, the interface impedance being basically the same as that of the bulk phase, and less accumulation of ohmic heat. At the same time, considering that the interface has the properties of LiCoO2 and is prone to structural collapse and electrolyte side reactions under high voltage conditions, to address this problem, the present invention stabilizes the crystal structure and does not deteriorate the ohmic heat by matching a specific content of Co element and controlling the mass ratio of X element to Co element.

[0060] In one embodiment, X is 100% Al element. Thus, the coating layer contains Co element and Al element, and the mass ratio of Al element to Co element in the coating layer is 25% - 50%.

[0061] In one embodiment, the total mass ratio of Co element and X element in the coating layer to the total mass of metal elements in the coating layer is more than 90%, and more preferably 95%. In the present invention, if other metals and other trace metal doping are not considered, the Co element and X element in the coating layer of the present invention can account for nearly 100% of the total mass of metal elements in the coating layer.

[0062] In one embodiment, when X is selected as 100% Al element, the total mass ratio of Co element and Al element in the coating layer to the total mass of metal elements in the coating layer is more than 90%, and more preferably 95%. In the present invention, if other metals and other trace metal doping are not considered, the Co element and Al element in the coating layer of the present invention can account for nearly 100% of the total mass of metal elements in the coating layer.

[0063] In one embodiment, the lithium cobalt oxide includes LiCoO2 and Li x Co 1-x O, where 0 < x < 1, and the content of LiCoO2 is greater than 76 wt.% and less than 100 wt.%, or the lithium cobalt oxide is 100 wt.% LiCoO2. Exemplarily, x can be 0.01, 0.03, 0.05, 0.07, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85 or 0.9, etc. The lithium-deficient phase Li x Co 1-x O has a layered structure. Whether the lithium cobalt oxide is LiCoO2 or Li x Co 1-xThe combination of O and LiCoO2 can facilitate the deintercalation of lithium ions and reduce the accumulation of ohmic heat.

[0064] The lithium cobalt oxide in the present invention does not contain Li a Co 1-a Co2O4, of which 0 <a<1,0<b<1。

[0065] In another embodiment, lithium cobalt oxide is composed of LiCoO2 and Li x Co 1-x O composition.

[0066] In one embodiment, the mass ratio of the X element in the coating layer to the Co element in the coating layer is 25% to 45%. Under this condition, the X element plays a more beneficial role.

[0067] In one embodiment, X further includes other coating elements, and the other coating elements are one or more of W, Ti and Ce.

[0068] In one embodiment, among the X elements, while ensuring that the Al element accounts for more than 50 wt.%, other matching elements, such as one or more of W, Ti and Ce, may be introduced as appropriate.

[0069] For the introduction of W and Ce, X includes Al, W and Ce at the same time. Al cooperates with W and Ce. W and Ce are used to further cooperate with Al to reduce the surface impedance of the coating layer, which is beneficial to further reduce the DC internal resistance of the battery cell. At the same time, if the content of W and Ce is too large, it will affect the high-temperature storage, high-rate charge and discharge performance of the battery cell. Therefore, it should be ensured that the Al element accounts for more than 50wt.% of the X element.

[0070] Regarding the introduction of Ti, X includes both Al and Ti at this time. Al and Ti cooperate, and Ti can further reduce the surface impedance of the coating layer, which is beneficial to further reduce the DC internal resistance of the battery cell. At the same time, if the Ti content is too large, the capacity of the battery cell will be reduced. Therefore, it should be ensured that the Al element accounts for more than 50wt.% of the X element.

[0071] In one embodiment of the present invention, there may also be a certain amount of Co source or cobalt compound after the reaction of Co source in the coating layer. The Co source or cobalt compound may include, for example, cobalt oxide, cobalt hydroxide, cobalt oxyhydroxide, etc. The Co source is generally an unreacted Co source when preparing the positive electrode material, and the cobalt compound is generally a substance formed by the reaction of the unreacted Co source during the second sintering process when preparing the positive electrode material. In one embodiment, the unreacted Co source accounts for less than 5% of the total mass of the Co source used in the coating process, preferably less than 2%, and more preferably close to 0%. Obviously, the unreacted or Co source, etc., has no obvious benefits or obvious damages for the coating, and is only generated by the sintering temperature in the preparation method, and belongs to the possible unreacted substances during the secondary sintering.

[0072] In another embodiment, the present invention provides a method for preparing the positive electrode material as described above, the preparation method comprising the following steps:

[0073] The positive electrode core and the coating source are mixed and then sintered, and the sintering temperature is greater than 500° C. and less than or equal to 800° C. to obtain the positive electrode material.

[0074] In the method for preparing a positive electrode material with a coating layer provided in one embodiment of the present invention, the sintering temperature is greater than 500°C and less than or equal to 800°C, for example, it can be 550°C, 600°C, 650°C, 700°C, 750°C or 800°C.

[0075] Wherein, the coating source includes a cobalt source and an X source, the X source includes an aluminum source, and more than 50wt.% of X is Al element. The preparation process of the positive electrode core is generally prepared by sintering a lithium source and other raw materials, and its surface generally has residual Li substances. The method of the present invention uses a coating source including a cobalt source and an aluminum source to mix and sinter the positive electrode core at high temperature. The Co element mainly reacts with the residual Li substance on the surface of the positive electrode core. Under the coordination of a specific content, a lithium cobalt compound containing more than 75wt.% of LiCoO2 can be formed, which can stabilize the crystal structure and have good lithium ion insertion and extraction dynamic performance, and will not deteriorate ohmic heat.

[0076] When the inventors completed the technical solution, they found that in the temperature range of greater than 500°C and less than or equal to 800°C, the cobalt source was basically reacted into lithium cobalt oxide during the secondary sintering process (the sintering involved in the preparation process of the positive electrode core is generally defined as primary sintering, then, the sintering here is defined as secondary sintering), and the mass of the unreacted cobalt source only accounts for less than 5% of the mass of the cobalt source used in the coating process, preferably less than 2%, and more preferably close to 0%.

[0077] From greater than 500℃ to less than or equal to 800℃, we can roughly observe the following rules: as the temperature increases, the content of LiCoO2 gradually increases, and Li x Co 1-x The content of O gradually decreases. When the temperature exceeds a certain value (for example, 650°C), the composition of lithium cobalt oxide is basically all LiCoO2 without Li x Co 1-x O.

[0078] In one embodiment, the cobalt source includes at least one of cobalt oxide, cobalt hydroxide, and cobalt oxyhydroxide.

[0079] In one embodiment, the aluminum source includes at least one of aluminum oxide, aluminum hydroxide, and aluminum oxyhydroxide.

[0080] In one embodiment, the X source further includes other coating sources, and the elements in the other coating sources are at least one of W, Ti and Ce.

[0081] In one embodiment, the other coating source is at least one of nitrate, chloride, hydroxide or oxide.

[0082] In one embodiment, the sintering is performed in an oxygen-containing atmosphere.

[0083] In one embodiment, the sintering time is 6h-24h, for example, it can be 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h, 21h, 22h, 23h or 24h.

[0084] In one embodiment, after the sintering is completed, the temperature is cooled at a cooling rate of 0.01°C / min to 3°C / min. For example, the cooling rate may be 0.01°C / min, 0.05°C / min, 0.1°C / min, 0.2°C / min, 0.5°C / min, 0.7°C / min, 1°C / min, 1.5°C / min, 2°C / min, 2.5°C / min or 3°C / min.

[0085] In one embodiment, the method for preparing the positive electrode core comprises the following steps:

[0086] The nickel-cobalt hydroxide, the doping source and the lithium source are mixed and sintered to obtain the positive electrode core.

[0087] The doping elements in the doping source include Al and A, wherein A includes one or more of Zr, Mg, Sr, Y, La, Nb, Ba and Ti.

[0088] In one embodiment, during the preparation of the positive electrode core, the molar ratio of each element satisfies that Li / (Ni + Co + Al + A) is 1 to 1.05.

[0089] In one embodiment, during the preparation of the positive electrode core, the sintering temperature is 400°C to 1000°C. For example, it can be 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C or 1000°C, etc.

[0090] In one embodiment, during the preparation of the positive electrode core, the sintering time is 6h to 20h. For example, it can be 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h or 20h, etc.

[0091] In another embodiment of the present invention, a lithium-ion battery is provided, which includes a positive electrode, a negative electrode and a separator, and the positive electrode includes the above-mentioned positive electrode material.

[0092] Based on the above embodiments, the following typical but non-limiting examples are provided:

[0093] Example 1

[0094] This example provides a positive electrode material with a coating layer. The positive electrode material with a coating layer includes a positive electrode core and a coating layer coated on the surface of the positive electrode core. The positive electrode core is a nickel-cobalt-aluminum ternary positive electrode material (chemical formula: Li 1.02 (Ni 0.88 Co 0.09 Al 0.03 )O2), the coating layer includes a lithium cobalt compound, and the lithium cobalt compound includes Li b Co 1-b O and LiCoO2, where 0 < x < 1. Based on the total mass of Li x Co 1-x O and LiCoO2 being 100 wt.%, the contents of Li x Co 1-x O and LiCoO2 are 15 wt.% and 85 wt.%, respectively; the coating layer also includes cobalt oxide, and the mass of cobalt oxide accounts for 2 wt.% of the total mass of the cobalt source (cobalt hydroxide + aluminum hydroxide) used in the coating process.

[0095] The coating layer also includes Al element, and the Al element exists in the form of Al2O3.

[0096] Based on the total mass of the positive electrode core, the content of Co element in the coating layer is 5000 ppm, and the content of Al element is 2000 ppm. Then, the mass ratio of Al element to Co element in the coating layer is 40%.

[0097] Figure 1 It is the scanning electron microscope image of the positive electrode material with a coating layer provided in this embodiment.

[0098] This embodiment also provides a preparation method of the above positive electrode material with a coating layer, including the following steps:

[0099] (1) Prepare the positive electrode core:

[0100] Mix nickel-cobalt hydroxide, doping source and lithium source and conduct primary sintering to obtain the positive electrode core; wherein, the doping source is aluminum oxide, the lithium source is LiOH, the molar ratio of Li / (Ni + Co + Al) is 1.02, the sintering temperature is 725 °C, and the sintering time is 16 h.

[0101] (2) Coating process:

[0102] Mix and grind the positive electrode core and the coating source. After grinding evenly, conduct secondary sintering. The sintering is carried out in an air atmosphere. The sintering temperature is 550 °C, the sintering time is 8 h, and after sintering is completed, cool down at a cooling rate of 1.5 °C / min to obtain the positive electrode material with a coating layer; wherein, the coating source is cobalt hydroxide and aluminum hydroxide.

[0103] Example 2

[0104] This embodiment provides a positive electrode material with a coating layer. The positive electrode material with a coating layer includes a positive electrode core and a coating layer coated on the surface of the positive electrode core. The positive electrode core is a nickel-cobalt-aluminum ternary positive electrode material (chemical formula: Li 1.02 (Ni 0.86 Co 0.10 Al 0.03 Zr 0.01 )O2), the coating layer includes a lithium cobalt compound, and the lithium cobalt compound includes Li x Co 1-x O and LiCoO2, where 0 < x < 1. Based on the total mass of Li x Co 1-x O and LiCoO2 being 100 wt.%, the contents of Li x Co 1-x O and LiCoO2 are 12 wt.% and 88 wt.%, respectively.

[0105] The coating layer also includes Al element, and the Al element exists in the form of Al2O3.

[0106] Based on the total mass of the positive electrode core, the content of Co element in the coating layer is 6000 ppm, and the content of Al element is 2000 ppm. Then, the mass ratio of Al element to Co element in the coating layer is 33.3%.

[0107] This embodiment also provides a preparation method of the above positive electrode material with a coating layer, including the following steps:

[0108] (1) Prepare the positive electrode core:

[0109] Mix nickel-cobalt hydroxide, doping source and lithium source and then conduct primary sintering to obtain the positive electrode core; wherein, the doping source is aluminum oxide and zirconium oxide, the lithium source is Li2CO3, the molar ratio of Li / (Ni + Co + Al) is 1.02, the sintering temperature is 730 °C, and the sintering time is 18 h.

[0110] (2) Coating process:

[0111] Mix and grind the positive electrode core and the coating source. After grinding evenly, conduct secondary sintering. The sintering is carried out in an oxygen atmosphere. The sintering temperature is 600 °C, the sintering time is 12 h, and after sintering is completed, cool down at a cooling rate of 0.5 °C / min to obtain the positive electrode material with a coating layer; wherein, the coating source is cobalt oxide and aluminum oxide.

[0112] Example 3

[0113] This embodiment provides a positive electrode material with a coating layer. The positive electrode material with a coating layer includes a positive electrode core and a coating layer coated on the surface of the positive electrode core. The positive electrode core is a nickel-cobalt-aluminum ternary positive electrode material (chemical formula: Li 1.05 (Ni 0.90 Co 0.09 Al 0.009 Mg 0.001 )O2), the coating layer includes a lithium-cobalt compound, and the lithium-cobalt compound includes Li x Co 1-x O and LiCoO2, where 0 < x < 1. Based on the total mass of Li x Co 1-x O and LiCoO2 being 100 wt.%, the contents of Li x Co 1-x O and LiCoO2 are 9 wt.% and 91 wt.%, respectively.

[0114] The coating layer also includes Al element, and the Al element exists in the form of Al2O3.

[0115] Based on the total mass of the positive electrode core, the content of Co element in the coating layer is 6500 ppm, and the content of Al element is 2500 ppm. Then the mass ratio of Al element to Co element in the coating layer is 38.5%.

[0116] This embodiment also provides a method for preparing the positive electrode material with a coating layer as described above, including the following steps:

[0117] (1) Prepare the positive electrode core:

[0118] Mix nickel-cobalt hydroxide, doping source and lithium source and then perform a primary sintering to obtain the positive electrode core; wherein, the doping source is aluminum oxide and magnesium oxide, the lithium source is Li2CO3, the molar ratio of Li / (Ni + Co + Al) is 1.05, the sintering temperature is 690 °C, and the sintering time is 14 h.

[0119] (2) Coating process:

[0120] Mix and grind the positive electrode core and the coating source, and then perform a secondary sintering after grinding evenly. The sintering is carried out in an oxygen atmosphere, the sintering temperature is 630 °C, the sintering time is 9 h, and after sintering is completed, the temperature is decreased at a rate of 0.5 °C / min to obtain the positive electrode material with a coating layer; wherein, the coating source is cobalt hydroxide and aluminum oxide.

[0121] Example 4

[0122] This embodiment provides a positive electrode material with a coating layer. The positive electrode material with a coating layer includes a positive electrode core and a coating layer coated on the surface of the positive electrode core. The positive electrode core is a nickel-cobalt-aluminum ternary positive electrode material (chemical formula: Li(Ni 0.83 Co 0.11 Al 0.05 Zr 0.002 Mg 0.002 La 0.002 Sr 0.004 )O2), and the coating layer includes a lithium cobalt compound. The lithium cobalt compound includes Li x Co 1-x O and LiCoO2, where 0 < x < 1, 0 < b < 1. Based on the total mass of Li x Co 1-x O and LiCoO2 being 100 wt.%, the contents of Li x Co 1-x O and LiCoO2 are 2 wt.% and 98 wt.%, respectively.

[0123] The coating layer also includes Al element, and the Al element exists in the form of Al2O3.

[0124] Based on the total mass of the positive electrode core, the content of the Co element in the coating layer is 7000 ppm, and the content of the Al element is 3000 ppm, and the mass ratio of the Al element to the Co element in the coating layer is 42.9%.

[0125] This embodiment also provides a method for preparing the positive electrode material having a coating layer, comprising the following steps:

[0126] (1) Preparation of positive electrode core:

[0127] Nickel cobalt hydroxide, a doping source and a lithium source are mixed and sintered once to obtain a positive electrode core; wherein the doping source is aluminum oxide, zirconium oxide, magnesium hydroxide, lanthanum oxide and strontium oxide, the lithium source is Li2CO3, the Li / (Ni+Co+Al) molar ratio is 1, the sintering temperature is 690°C, and the sintering time is 14 hours.

[0128] (2) Coating process:

[0129] The positive electrode core and the coating source are mixed and ground, and after grinding evenly, secondary sintering is performed. The sintering is performed in an air atmosphere at a temperature of 650°C and a sintering time of 6 hours. After sintering, the temperature is cooled at a cooling rate of 0.6°C / min to obtain a positive electrode material with a coating layer; wherein the coating source is cobalt oxide and aluminum oxide.

[0130] Example 5

[0131] This embodiment provides a positive electrode material with a coating layer, wherein the positive electrode material with a coating layer comprises a positive electrode core and a coating layer coated on the surface of the positive electrode core, wherein the positive electrode core is a nickel-cobalt-aluminum ternary positive electrode material (chemical formula is Li 1.04 (Ni 0.92 Co 0.07 Al 0.01 )O2), the coating layer includes a lithium cobalt compound, and the lithium cobalt compound is LiCoO2.

[0132] The coating layer also includes Al element, and the Al element exists in the form of Al2O3.

[0133] Based on the total mass of the positive electrode core, the content of Co in the coating layer is 8000 ppm, the content of Al is 300 ppm, and the content of W is 500 ppm. The mass ratio of the total content of Al and W elements in the coating layer to the Co element is 43.75%.

[0134] This embodiment also provides a method for preparing the positive electrode material having a coating layer, comprising the following steps:

[0135] (1) Preparation of positive electrode core:

[0136] Nickel cobalt hydroxide, a doping source and a lithium source are mixed and sintered once to obtain a positive electrode core; wherein the doping source is aluminum oxide, the lithium source is Li2CO3, the Li / (Ni+Co+Al) molar ratio is 1.04, the sintering temperature is 690°C, and the sintering time is 14 hours.

[0137] (2) Coating process:

[0138] The positive electrode core and the coating source are mixed and ground, and after grinding evenly, secondary sintering is performed. The sintering is performed in an oxygen atmosphere at a temperature of 700°C and a sintering time of 10 hours. After sintering, the temperature is cooled at a cooling rate of 2°C / min to obtain a positive electrode material with a coating layer; wherein the coating source is cobalt oxide, aluminum oxide and tungsten oxide.

[0139] Example 6

[0140] This embodiment provides a positive electrode material with a coating layer, wherein the positive electrode material with a coating layer comprises a positive electrode core and a coating layer coated on the surface of the positive electrode core, wherein the positive electrode core is a nickel-cobalt-aluminum ternary positive electrode material (chemical formula is Li 1.02 (Ni 0.90 Co 0.07 Al 0.02 La 0.005 )O2), the coating layer includes a lithium cobalt compound, and the lithium cobalt compound is LiCoO2.

[0141] The coating layer also includes Al element, and the Al element exists in the form of Al2O3.

[0142] Based on the total mass of the positive electrode core, the content of Co in the coating layer is 8000ppm, the content of Al is 3000ppm, and the content of W is 500ppm. The mass ratio of the total content of Al and W elements in the coating layer to the Co element is 43.75%.

[0143] This embodiment also provides a method for preparing the positive electrode material having a coating layer, comprising the following steps:

[0144] (1) Preparation of positive electrode core:

[0145] Nickel cobalt hydroxide, a doping source and a lithium source are mixed and sintered once to obtain a positive electrode core; wherein the doping source is aluminum oxide and lanthanum oxide, the lithium source is Li2CO3, the Li / (Ni+Co+Al) molar ratio is 1.02, the sintering temperature is 600°C, and the sintering time is 14 hours.

[0146] (2) Coating process:

[0147] The positive electrode core and the coating source are mixed and ground, and after grinding evenly, secondary sintering is performed. The sintering is performed in an oxygen atmosphere at a temperature of 800°C and a sintering time of 10 hours. After sintering, the temperature is cooled at a cooling rate of 2°C / min to obtain a positive electrode material with a coating layer; wherein the coating source is cobalt oxide, aluminum oxide and tungsten oxide.

[0148] Comparative Example 1

[0149] This comparative example provides a positive electrode material with a coating layer. Compared with Example 1, the difference is that, based on the total mass of the positive electrode core, the content of the Co element in the coating layer is 4000ppm, and the content of the Al element is 3000ppm, then the mass ratio of the Al element to the Co element in the coating layer is 75%; the types and contents of the Co element and the X element in the coating layer are shown in Table 1.

[0150] Comparative Example 2

[0151] This comparative example provides a positive electrode material with a coating layer. Compared with Example 1, the only difference is that, based on the total mass of the positive electrode core, the content of the Co element in the coating layer is 5800ppm, and the content of the Al element is 1200ppm, then the mass ratio of the Al element to the Co element in the coating layer is 20.7%; the types and contents of the Co element and the X element in the coating layer are shown in Table 1.

[0152] Comparative Example 3

[0153] This comparative example provides a positive electrode material with a coating layer. Compared with Example 1, the difference is that, based on the total mass of the positive electrode core, the content of the Co element in the coating layer is 1000ppm, and the content of the Al element is 4000ppm, then the mass ratio of the Al element to the Co element in the coating layer is 400%; the types and contents of the Co element and the X element in the coating layer are shown in Table 1.

[0154] Comparative Example 4

[0155] This comparative example provides a positive electrode material with a coating layer. Compared with Example 1, the difference is that, based on the total mass of the positive electrode core, the content of the Co element in the coating layer is 8500ppm, and the content of the Al element is 2000ppm, then the mass ratio of the Al element to the Co element in the coating layer is 23.5%; the types and contents of the Co element and the X element in the coating layer are shown in Table 1.

[0156] Comparative Example 5

[0157] This comparative example provides a positive electrode material with a coating layer. Compared with Example 1, the difference is that, based on the total mass of the positive electrode core, the content of the Co element in the coating layer is 3000 ppm, and the content of the Al element is 1000 ppm, then the mass ratio of the Al element to the Co element in the coating layer is 33.3%; the types and contents of the Co element and the X element in the coating layer are shown in Table 1.

[0158] Comparative Example 6

[0159] This comparative example provides a positive electrode material with a coating layer. Compared with Example 1, the difference is that, based on the total mass of the positive electrode core, the content of the Co element in the coating layer is 10000 ppm, and the content of the Al element is 4000 ppm, then the mass ratio of the Al element to the Co element in the coating layer is 25.0%; the types and contents of the Co element and the X element in the coating layer are shown in Table 1.

[0160] Table 1

[0161]

[0162] Prepare the battery:

[0163] (1) Preparation of positive electrode sheet:

[0164] The positive electrode materials of Examples 1-6 and Comparative Examples 1-6 were used as active materials, and the active materials were mixed with a conductive agent Super P and a binder PVDF in NMP at a mass ratio of 95:2:3 to obtain a positive electrode slurry. The positive electrode slurry was coated on the surface of an aluminum foil and dried to obtain a positive electrode sheet.

[0165] (2) Preparation of negative electrode sheet:

[0166] The artificial graphite negative electrode, the conductive agent Super P, the binder CMC, and the thickener SBR were mixed in water at a mass ratio of 96:0.5:1.5:2 to obtain a negative electrode slurry. The negative electrode slurry was coated on the surface of the copper foil and dried to obtain a negative electrode sheet.

[0167] (3) Providing a diaphragm and an electrolyte, wherein the diaphragm is a multilayer composite diaphragm, the substrate material is a polyolefin polymer, and the composite material is a high heat-resistant inorganic ceramic; the electrolyte is obtained by dissolving LiPF6 in a mixed solvent of EC, DMC and FEC, wherein the mass ratio of EC:DMC:FEC:LiPF6 is 20:60:5:15.

[0168] (4) The positive electrode sheet, negative electrode sheet and separator are wound up, placed in a battery case and injected with electrolyte to obtain a battery.

[0169] To perform a performance test on the battery:

[0170] (1) Test cycle performance: at room temperature 25°C, charge at 2C, discharge at 10C, cycle 600 times, calculate capacity retention rate, capacity retention rate = 600th cycle discharge capacity / first cycle discharge capacity × 100%.

[0171] (2) Test the maximum temperature of a fully charged cell: The test is carried out in a hot box at a temperature of 133°C.

[0172] (3) Test the maximum temperature of a single cell when it is overcharged to 6V at 5C, the CID opening time, and check whether the cell catches fire or explodes. Among them, the maximum temperature of a single cell when it is overcharged to 6V at 5C reflects the heat generation, and the CID opening time reflects the gas generation. A delayed CID opening time indicates less gas generation. At the same time, the present invention hopes that the CID will open when the overcharge is close to 5V, so the CID opening time should not be too early or too late. If it is opened too early, it will show that the CID has been opened before the battery is charged to 5V, and the cell is disconnected, which will prematurely cause the battery or even the battery pack to fail. However, if it is opened too late, the battery is prone to overheating and explosion. At this time, the overcharge voltage of the battery has obviously seriously exceeded 5V, and the battery will be in a very critical state.

[0173] See Table 2 for the results.

[0174] Table 2

[0175]

[0176] It can be seen from Table 2 that by using a coating layer to coat the high-nickel nickel-cobalt-aluminum-based ternary positive electrode material, and controlling the content of the Co element in the coating layer to be 4000ppm~8000ppm, the content of LiCoO2 in the lithium cobalt oxide in the coating layer is greater than 75wt.%, and the mass ratio of the X element to the Co element is 25%~50%. While stabilizing the crystal structure, it is beneficial to the transmission of lithium ions, reduces the accumulation of ohmic heat, reduces gas production, and improves the safety performance of the battery.

[0177] The 18650 cylindrical battery cells assembled from the positive electrode materials of Examples 1-6 have a 2C / 10C cycle 600-cycle capacity retention rate of >84%, the maximum temperature of the fully charged battery cells is above 134°C, and there is no gas discharge due to gas production, and the CID opening time is between 750s and 820s, which not only avoids premature battery failure, but also avoids the risk of explosion. Moreover, even when a single battery cell is overcharged to 5V at 5C, the maximum temperature exceeds 100°C, and it will not catch fire or explode.

[0178] In Comparative Example 1, since the cobalt content in the coating layer is 4000ppm and the Al content in the coating layer is 3000ppm, the mass ratio of Al to Co in the coating layer is 75%, which exceeds the upper limit of 50% in product design. Although the increase of Al protects the stability of the interface during the overcharging process of the battery cell, it also reduces the gas production designed to open the CID and worsens the impedance of the battery cell, which ultimately leads to the CID opening time being too late (889s) during the overcharging process of the battery cell, and the overall temperature rise of the battery cell is too high, leading to explosion (Experiment 3).

[0179] In Comparative Example 2, since the cobalt content in the coating layer is 5800ppm and the Al content in the coating layer is 1200ppm, the mass ratio of Al to Co in the coating layer is 20.7%, which is lower than the lower limit of 25% of the product design. Due to the lack of Al, the interface protection is insufficient, resulting in a drop in the cycle capacity retention rate to 80%, and an explosion in Experiment 2. In Experiment 3, due to insufficient interface protection and excessive gas production, the CID opened prematurely. Although there was no explosion, the battery failed prematurely and did not meet the product design requirements.

[0180] In Comparative Example 3, since the cobalt content in the coating layer is 1000ppm, and the Al content in the coating layer is 4000ppm, the mass ratio of Al to Co in the coating layer is 400%, and the cobalt content is lower than the lower limit of 4000ppm required by the design. The lack of Co leads to a significant increase in the overall impedance of the battery cell. In Experiment 3, the increase in impedance causes the battery cell temperature to rise too quickly, and eventually explodes.

[0181] In Comparative Example 4, since the content of cobalt in the coating layer is 8500ppm and the content of Al in the coating layer is 2000ppm, the mass ratio of Al to Co in the coating layer is 23.5%, and the content of cobalt exceeds the upper limit of 8000ppm. The increase in the amount of Co in the coating layer requires Al to provide corresponding protection, but the Al content in Comparative Example 4 is also insufficient, resulting in insufficient interface protection, excessive gas production, and premature opening of the CID. Moreover, the capacity retention rate decreased, and it exploded in Experiment 2.

[0182] In the present invention, the Co content of 4000ppm~8000ppm is verified by a large number of experiments and theoretical designs. Too low (Comparative Example 3) or too high (Comparative Example 4) Co content cannot balance the two properties of impedance and gas production, thereby causing failure of the battery cell design. At the same time, the introduction of Al and X elements is to protect the interface of the coating layer, and Al or X elements need to be used in conjunction with Co elements.

[0183] In Comparative Example 5, the Co content in the coating layer is less than 4000ppm. Although the mass ratio of Al element to Co element in the coating layer is between 25% and 50%, the amount of Al is also reduced due to the lack of Co. They provide insufficient interface protection and the impedance is not improved. Both the impedance and interface improvement are deteriorated. Therefore, the retention rate is reduced to 79%. Experiment 2 explodes, and Experiment 3 produces more gas. Although the CID is opened in advance, it still explodes. All performances of Comparative Example 5 are deteriorated.

[0184] In comparative example 6, the Co content in the coating layer is greater than 8000ppm. Although the mass ratio of Al element to Co element in the coating layer is between 25% and 50%, since the content of Co is 10000ppm and Al is 4000ppm, the content of Co exceeds the upper limit of 8000ppm designed for the product. At a coating temperature of 500℃ to 800℃, most of the final compounds of Co are converted into LiCoO2, which leads to a substantial increase in LiCoO2. This substance is unstable at high temperature and high voltage and is prone to explosion. Therefore, the product design of the present invention needs to strictly restrict the content of Co, which must not exceed 8000ppm. Therefore, although the cycle retention rate of comparative example 6 is OK (capacity retention rate 84%), experiment 2 explodes and experiment 3 also explodes. It can be seen from comparative example 6 that although the mass ratio of Al element to Co element in the coating layer is within the interval range, the content of Co exceeds the upper limit, and the total amount of LiCoO2 generated exceeds the upper limit of the design, resulting in a decrease in the thermal stability of the battery cell and loss of control.

[0185] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0186] The present invention illustrates the detailed method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed method, that is, it does not mean that the present invention must rely on the above-mentioned detailed method to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A positive electrode material, characterized in that: The positive electrode material comprises a positive electrode core and a coating layer coated on the surface of the positive electrode core, and the chemical composition of the positive electrode core is Li α Ni x Co y Al z A m O2, 1≤α≤1.05, 0.80≤x≤0.95, 0.04≤y≤0.15, 0.005≤z≤0.06, 0≤m≤0.02, x+y+z+m=1, wherein A includes one or more of Zr, Mg, Sr, Y, La, Nb, Ba and Ti; The coating layer contains Co and X elements, the mass proportion of the X element in the coating layer relative to the Co element in the coating layer is 25% to 50%; X is a metal element different from Co, and more than 50wt.% of X is Al element; The coating layer includes lithium cobalt oxide, and the lithium cobalt oxide includes LiCoO2 with a content greater than 75wt.%; Based on the total mass of the positive electrode core, the content of the Co element in the coating layer is 4000ppm~8000ppm.

2. The positive electrode material according to claim 1, characterized in that The lithium cobalt oxide includes LiCoO2 and Li x Co 1- x O, where 0 < x < 1, and the content of LiCoO2 is greater than 76 wt.% and less than 100 wt.%, or the lithium cobalt oxide is 100 wt.% LiCoO2; and / or, The mass proportion of the X element in the coating layer relative to the Co element in the coating layer is 25% to 45%.

3. The positive electrode material according to claim 1, characterized in that X is 100 wt.% of Al element; and / or, X also includes other coating elements, and the other coating elements are one or more of W, Ti and Ce.

4. A method for preparing a positive electrode material according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: The positive electrode core and the coating source are mixed and then sintered, wherein the sintering temperature is greater than 500° C. and less than or equal to 800° C., to obtain a positive electrode material; The coating source includes a cobalt source and an X source, the X source includes an aluminum source, and more than 50 wt.% of X is Al element.

5. The preparation method according to claim 4, characterized in that: The cobalt source comprises at least one of cobalt oxide, cobalt hydroxide and cobalt oxyhydroxide; and / or, The aluminum source includes at least one of aluminum oxide, aluminum hydroxide, and aluminum oxyhydroxide.

6. The preparation method according to claim 4, characterized in that: The X source also includes other coating sources, and the elements in the other coating sources are at least one of W, Ti and Ce; and / or, The other coating source is at least one of nitrate, chloride, hydroxide or oxide.

7. The preparation method according to claim 4, characterized in that: The sintering is performed in an oxygen-containing atmosphere; and / or, The sintering time is 6h~24h; and / or, After the sintering is completed, the temperature is lowered at a cooling rate of 0.01° C. / min to 3° C. / min.

8. The preparation method according to claim 4, characterized in that: The method for preparing the positive electrode core comprises the following steps: The nickel-cobalt hydroxide, the doping source and the lithium source are mixed and sintered to obtain a positive electrode core; The doping elements in the doping source include Al and A, wherein A includes one or more of Zr, Mg, Sr, Y, La, Nb, Ba and Ti.

9. The preparation method according to claim 8, characterized in that: During the preparation of the positive electrode core, the molar ratio of each element satisfies Li / (Ni+Co+Al+A) of 1 to 1.05; and / or, During the preparation of the positive electrode core, the sintering temperature is 400° C. to 1000° C.; and / or, During the preparation of the positive electrode core, the sintering time is 6h~20h.

10. A lithium ion battery comprising a positive electrode, a negative electrode and a separator, characterized in that: The positive electrode comprises the positive electrode material according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • Double-gradient coated high-nickel ternary cathode material and preparation method thereof

    CN110970601A

  • Multi-element-coated modified single-crystalline nickel cobalt lithium manganate positive electrode material, preparation method therefor and lithium ion battery

    WO2024140211A1